Modern soccer industry management and current challenges: systematic literature review - Daniel Getnet; Zelalem Melkamu; Sisay Mengistu (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Soccer is known as the "global game" because it is very popular in many parts of the world. Numerous studies have been conducted in different parts, segments, and levels of the soccer industry. However, the findings are inconclusive, unidirectional, and contradictory.